Methods for Predicting Speed of Sound in Fatty Acid Ethyl Esters and Ethylic Biodiesels Using Gibbs Energy Additivity - Natakron Sirimongkolgal; Mana Amornkitbamrung; Suriya Phankosol (International Journal of Chemical Engineering)
The speed of sound has a considerable influence on the parameters of fuel injection. It depends on the link between the fatty acid ethyl ester and the molecular structure and temperature. This study presents Gibbs energy additivity methods for predicting the speed of sound in saturated or unsaturated fatty acids, ethyl ester, or an ethylic biodiesel based on either (1) the number of carbon atoms (z) and number of double bonds (nd) of the fatty acid or (2) the saponification number (SN) and iodine value (IV) of the fatty acid. The proposed equations are straightforward to apply, and the estimated speed of sound values of pure fatty acid ethyl esters and ethylic biodiesels at various temperatures match the reported values well. Estimation using the proposed method is possible without knowing the sound speed of each fatty acid ethyl ester component in biodiesel.